Analysis of Cash Flow Statements Using Sharia Accounting Principles as a Tool for Measuring Investment Decisions - Yunisa, Widya; K, Kamilah; Nasution, Yenni Samri Juliati (Ilomata International Journal of Management, 2024)
The purpose of this study was to determine the application of sharia accounting principles in analyzing cash flow statements can be used as an effective tool for measuring and making investment decision decisions at PT Adhi Karya (Persero) Tbk. This research uses a qualitative approach with descriptive methods. Data obtained from the company's cash flow statement in the period 2019-2023. The results of the analysis of the cash flow statement at PT Adhi Karya (Persero) Tbk show the use of the ratio analysis method, by paying attention to several key ratios. Liquidity ratios, such as Operating Cash Flow (OCF), show figures of 2%, 5%, 5%, 5%, 0%. The Funds Flow Coverage Ratio (CAD) has values of 1.61 times, 0.70 times, 0.89 times, 0.85 times, 0.81 times. The ratio of Operating Cash Flow to Interest (OCF) has a value of 2.62 times, 3.77 times, 3.57 times, 3.48 times, 2.54 times. The Capital Expenditure (CPE) ratio reached 2,136.60 times, 5,395.08 times, 3,770.59 times, 1,296.07 times, 273.36 times. Meanwhile, the Total Debt (TH) ratio ranged from 2%, 4%, 4%, 4%, 0%. In addition, the results of the Cash Flow Adequacy Flexibility Ratio (ACC) show values of 0.020 times, -0.015 times, -0.004 times, -0.006 times, -0.012 times. From this analysis, investment decisions can be made based on the performance of the cash flow statement of PT Adhi Karya (Persero) Tbk, indicating that the company's financial reporting reflects compliance with Islamic accounting principles. Fairness and accountability in the company's liquidity reflect accountability.